Homosexually active Latino men : issues for social work practice - Zamora-Hernándes, Carlos E.; Patterson, Davis G. (Journal of gay [and] lesbian social services : issues in practice, policy [and] research)
"Carlos E. Zamora-Hernándes, Davis G. Patterson Fonds Suzan Daniel (FSD)"